Arena pública e patrimônio cultural: Praça do Carmo Belém/PA, no contexto das manifestações culturais Auto do Círio e Arrastão do Círio - ANDRADE, Helly Tayana de Souza (2019)
The research brings the discussion and public equity arena, in order to understand the social relations and forms of use that the actors attribute to the Carmo Square, also investigated how to give the Arenas Public according to the cultural events that took place in the Square Carmo and extensions of the historic center. To encourage the public arena discussions in a public space and tumbled were used as methodology, data collection techniques such as direct observation and notes in a diary, documentary and bibliographical research and applied a script for interviews. From these techniques it was possible to achieve the results presented in this paper: from the logic of engagement presented by Cefai; Veiga and Mota (2011) stood out the logic of social cohesion and personal fulfillment, cohesion as a propagator of sense of citizenship and draws attention to the rights and duties of those who share the space of the Carmo Square, the personal achievement is presented as a source of motivation for the interviewed participants of cultural events Auto Cirio and Dragnet's Cirio; forms of use of public space generates conflicts because according to Cefai authors ; Veiga and Mota , in the process are involved a series of effectivities , sensibilities and collective moralities ; involves trials of feelings of love, hate, fear, injustice , hope, fate , enthusiasm and disorder , which are already ways of defining social situations and already touch the common sense ( Cefaï ; Veiga and Mota 2011 , p 31) . ; and it is for this reason that the publicity process is very important because that is when all stakeholders will expose the problem situation and discuss possible solutions to it and how it was identified that happens in the Carmo Square by meetings between community organizers cultural manifestations competent authorities . Thus the final considerations cover the concepts of Lefeve (2006) which focuses on the idea of designed space that would be one that the public can systematically designed, living space than that which is characterized by community ownership who comes to forms of use not systematically design for that location and the perceived space that space characterized by the appropriation of cultural events; research can also complete supported by bibliography Goffeman (2010), the Nazareth Taper can be understood within the concept of social occasion, in this review the cultural events can be interpreted as social situations and finally the set of two or more members performing an action or activity within social situations characterize social gatherings. In this way it was possible to analyze the conflicts that occur in favor of the use of space of the Carmo Square that give rise to public arenas and trigger a series of problem situations that require discursões to substantiate their speeches to maintain the presence of all stakeholders, speeches those who are linked to the heritage, culture and citizenship.